Persepsi Konsumen terhadap Penggunaan Media Sosial Starbucks dalam Pembentukan Brand Image - Dewi, Anak Agung Istri Reginata; Latupeirissa, Jonathan Jacob Paul; Sari, Ni Putu Intan Permata; Pratiwi, Nuning Indah (JURNAL ILMIAH EDUNOMIKA, 2025)
Social media has become an important platform in everyday life and a strategic tool for companies to build brand image, which is crucial for customer loyalty and business success in a competitive market. However, there is still a gap in understanding how this platform comprehensively affects brand loyalty and the specific mechanisms behind it. This study aims to analyze consumer perceptions of Starbucks' use of social media in shaping its brand image, using a descriptive qualitative method with in-depth interviews with nine informants. The results show that social media is effective in building Starbucks' image as a symbol of modern lifestyle, with content that is perceived as attractive and professional, increasing awareness and purchase intent. However, consumer interactions tend to be passive (lurking) due to content overload, social media fatigue, and preferences for other platforms. In conclusion, Starbucks needs to innovate in its content and distribution strategies to transform passive consumption into active engagement amid increasingly fierce competition. Further research is recommended to explore brand loyalty across various social media platforms and its driving factors.